Targets and mechanisms of Alpinia oxyphylla Miquel fruits in treating neurodegenerative dementia - Zeng, Peng; Liu, Yuan-Cheng; Wang, Xiao-Ming; Ye, Chao-Yuan; Sun, Yi-Wen; Su, Hong-Fei; Qiu, Shuo-Wen; Li, Ya-Nan; Wang, Yao; Wang, Yan-Chun; Ma, Jun; Li, Man; et al. (Frontiers in Aging Neuroscience, 2022)
The dried and ripe fruits of Alpinia oxyphylla and ripe fruits of Alpinia oxyphylla Miquel (AO) have the effects of tonifying kidney-essence and nourishing intelligence and thus have been widely used in treating dementia. Alzheimer’s disease (AD) is a typical form of neurodegenerative dementia with kidney-essence deficiency in Traditional Chinese Medicine (TCM). So far, there is a lack of systematic studies on the biological basis of tonifying kidney-essence and nourishing intelligence and the corresponding phytochemicals. In this study, we investigated the targets of AO in tonifying kidney-essence and nourishing intelligence based on the key pathophysiological processes of neurodegenerative dementia. According to ultra-high-performance liquid chromatography with triple quadrupole mass spectrometry data and Lipinski’s rule of five, 49 bioactive phytochemicals from AO were identified, and 26 of them were found to target 168 key molecules in the treatment of neurodegenerative dementia. Nine phytochemicals of AO were shown to target acetylcholinesterase (ACHE), and 19 phytochemicals were shown to target butyrylcholinesterase (BCHE). A database of neurodegenerative dementia with kidney-essence deficiency involving 731 genes was constructed. Furthermore, yakuchinone B, 5-hydroxy-1,7-bis (4-hydroxy-3-methoxyphenyl) heptan-3-one (5-HYD), oxyhylladiketone, oxyphyllacinol, butyl-β-D-fructopyranoside, dibutyl phthalate, chrysin, yakuchinone A, rhamnetin, and rhamnocitrin were identified as the key phytochemicals from AO that regulate the pathogenesis of neurodegenerative dementia in a multitargeted manner. The approach of studying the pharmacological mechanism underlying the effects of medicinal plants and the biological basis of TCM syndrome may be helpful in studying the translation of TCM.